Comment to the paper: To replicate or not to replicate, or when did we start to ignore the concept of statistical power?. (January 2020) - Berget, Ingunn
Highlights: Replicates are needed for analysing individual differences. Replicates are needed quality control of sensory data. Accuracy not always required. Replication structure may influence the statistical analysis.